“FAKE NEWS”: THE (MIS)PATHS OF POLITICAL COMMUNICATION AND NEW LEGAL CONTROL TOOLS SPONSORED BY THE ADVERTISING RESOLUTION OF THE SUPERIOR ELECTORAL TRIBUNAL IN THE 2022 ELECTIONS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The dissemination of “fake news” does not appear as an innovative event, but modified by new technological means. In a disconnected society that can manipulate society to connect, see society in another way to connect and to connect to others disconnected. Considering this and the timid means available to effectively combat this phenomenon, repressive and preventively active, Resolution of the Superior Electoral Court n. . It is understood that the Electoral's attempts to close the siege to justification-information are valid, even if their validity is not subject to adequate prediction, given the novelties.